عہد نبویﷺ اور خلافت راشدہ میں علوم وفنون کی ترویج کا تجزیاتی مطالعہ: Urdu: Educational Development in the Period of the Prophetﷺ and the Rashidun Caliphs (Al Basirah, 2023)
This research paper examines the educational development that took place during the period of the Prophet Muhammadﷺ and the Rashidun Caliphs. By analyzing historical accounts, primary sources, and scholarly works, the study explores the initiatives and practices to promote education and knowledge acquisition in early Islamic society. The research highlights the Prophet Muhammad'sﷺ emphasis on the pursuit of knowledge and his role as a teacher, mentor, and inspirer of learning. His focus on establishment of educational institutions such as the "Suffah" and the encouragement of companions to seek and disseminate knowledge from the Prophetﷺ. Furthermore, the paper focuses the educational policies and reforms implemented by the Rashidun Caliphs, including the establishment of schools, libraries, and centers of learning. The study also examines the inclusiveness of the educational system, which provided opportunities for both men and women to engage in learning. Moreover, the research highlights the integration of moral and ethical teachings within the educational curriculum, aiming to develop well-rounded individuals who exemplify virtuous conduct. The findings of this research shed light on the significance of education in early Islamic society and its impact on the intellectual and social development of the community.
Keywords: Centers of learning; Contemporary Educational Systems; Culture of learning; Educational development; Intellectual and social development; Suffah